Differential effects of insulin sensitization and insulin provision treatment strategies on concentrations of circulating adipokines in patients with diabetes and coronary artery disease in the BARI 2D trial. (29th August 2020) - Wolk, Robert; Bertolet, Marnie; Brooks, Maria M; Pratley, Richard E; Sobel, Burton E; Frye, Robert L; Singh, Prachi; Calvin, Andrew D; Rutter, Martin K; Mooradian, Arshag D; Somers, Virend K; ,
Abstract: Aims: To determine the effects of insulin sensitization (IS) and insulin provision (IP) treatment strategies on adipokines associated with cardiovascular disease in patients with type 2 diabetes mellitus and coronary artery disease in the Bypass Angioplasty Revascularization Investigation 2 Diabetes trial (BARI 2D). Methods and results: Changes in adipokine levels were compared in patients with type 2 diabetes mellitus and coronary artery disease randomized to IS ( n = 1037) versus IP ( n = 1019) treatment strategies in BARI 2D. Circulating concentrations of leptin, adiponectin, monocyte chemoattractant protein-1, tumor necrosis factor-alpha, interleukin 6 and C-reactive protein were evaluated at baseline and one year. IS and IP treatment strategies exerted significant ( p < 0.0001) differential effects on: leptin (IS: 0.02% decrease, p = 0.01; IP: 13% increase, p < 0.0001); adiponectin (IS: 73% increase, p < 0.0001; IP: no change, p = 0.52); interleukin 6 (IS: 14% decrease, p < 0.0001; IP: no change, p = 0.68). Changes in monocyte chemoattractant protein-1 and tumor necrosis factor-alpha were not statistically different between groups. C-reactive protein decreased, but the effect was significantly greater in the IS group (–32%, p < 0.0001) than in the IP group (–5%, p = 0.0005). Conclusion: The IS and IP treatment strategies exerted divergent effects on adipokine and inflammatory profile in patients with type 2 diabetes mellitus and coronary artery disease. The IS treatment strategy-induced changes may be more favorable than the IP treatment strategy regarding cardiovascular pathophysiology.